2016
DOI: 10.3892/ol.2016.4313
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-187 induces diffuse large B-cell lymphoma cell apoptosis via targeting BCL6

Abstract: Abstract. MicroRNAs (miRs) are endogenous non-coding RNAs that serve key functions in a wide range of biological processes, including cell growth, development, apoptosis and carcinogenesis. However, the association between miR-187 and B-cell lymphoma 6 (BCL6) has yet to be fully investigated in lymphoma cell apoptosis. The present study hypothesized that a post-translational mechanism may exist for BCL6 expression, which is regulated by miR-187 in lymphoma cells. The present study demonstrated that the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…miR-187 suppresses lung cancer development by targeting Bcl6 (51). Consistently, the targeting of Bcl6 by miR-187 also functions in regulating diffuse large B-cell lymphoma cell apoptosis (52). Here, our study for the first time reported that miR-10b is a novel miRNA that targets and modulates Bcl6 expression in osteoblasts.…”
Section: Discussionsupporting
confidence: 74%
“…miR-187 suppresses lung cancer development by targeting Bcl6 (51). Consistently, the targeting of Bcl6 by miR-187 also functions in regulating diffuse large B-cell lymphoma cell apoptosis (52). Here, our study for the first time reported that miR-10b is a novel miRNA that targets and modulates Bcl6 expression in osteoblasts.…”
Section: Discussionsupporting
confidence: 74%
“…miR-187 has been reported to be related to certain types of cancer and other diseases. [ 31 , 32 ] For instance, Zhang et al showed that decreased miR-187 expression could induce retinal ganglion cell apoptosis through upregulating SMAD Family Member 7 (SMAD7) in glaucoma. [ 32 ] In accordance with this study, we determined that the target genes of miR-187-3p could be enriched in the positive regulation of cell proliferation, suggesting that miR-187-3p may play a critical role in regulating cell proliferation and apoptosis associated with the progression of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…UTR variants on BCL6 (apoptosis-regulating transcription factor) in this study, we suggest that the interaction of targeting microRNAs, including microRNA-10a, 59 microRNA-187, 60 and microRNA-187-3p 61 should be further investigated in prostate cancer. As transcription factors and microRNAs are master regulators of cell systems biology, transcription factor-microRNA interactions are clearly of high impor-tance in cancer studies.…”
Section: Discussionmentioning
confidence: 74%